Hubungan Antara Kecerdasan Intelegensi (IQ) dengan Hasil Belajar Matematika Siswa Kelas X SMAN 1 Woha - Nur Syariful Amin (SUPERMAT : Jurnal Pendidikan Matematika, 2021)
Intelligence as a cognitive element plays an important role in influencing student achievement. In the intelligence test there are aspects that reveal logical, rational and memorizing thinking, so that intelligence becomes an internal factor in improving student learning outcomes. This study aims to determine whether there is a relationship between intelligence and mathematics learning outcomes for class X SMA Negeri 1 Woha in the academic year 2020/2021. The research method used is the simple correlation and regression method. This study uses 2 variables, namely variable (X) Intelligence and variable (Y) Mathematics learning outcomes. The subjects of this study were 33 students of class X SMA Negeri 1 Woha in the 2020/2021 academic year. consisting of 18 female students and 15 male students. The data collection method for variable X uses intelligence test results data and variable Y data uses the results of the latest report cards for students' math scores in the odd and even semesters of the 2020/2021 school year. The results showed that there was a relationship between intelligence and mathematics learning outcomes for class X students of SMA Negeri 1 Woha with the results of the Pearson correlation calculation of rcount = 6.35 and rtable = 2.03. While the calculation of the simple linear regression equation shows the results of = 22.74 + 0.535X, which means that the influence of the two variables is positive.